Culture and art - Bauman, Zygmunt 1925-2017 (polity, 2021)
"Previously unpublished writings on culture and art by one of the most influential social thinkers of our time"--
Keywords: Bauman, Zygmunt -- 1925-2017; Kulturtheorie; Kunstsoziologie; Arts and society; Quelle